IMPELEMENTASI KURIKULUM MERDEKA TERHADAP TANTANGAN DAN KEPUASAN BAGI GURU PAI DI SDN SERANG 21 KOTA SERANG - Maslihah, Maslihah; Supardi, Supardi; Bachtiar, Machdum; Syakib, Najmi; Wasehudin, Wasehudin (Fakultas Agama Islam Universitas Ibn Khaldun Bogor, 2023)
The government through the ministry of education appealed to all educational institutions to implement an independent curriculum. This needs to be responded well by all educational practitioners in an effort to achieve the success of educational goals. Thus the purpose of this study is to reveal the challenges and satisfactions of PAI teachers at SDN 21 Kota Serang in implementing the independent curriculum. Qualitative method with the type of field research. Data collection techniques through participatory observation and interviews. To reveal the results of the data on the level of satisfaction and hands in this study, a SWOT analysis was used. The results of this study explain that the implementation of the independent curriculum at SDN Serang 21 independently changes by using the teaching tools that have been provided according to the independent curriculum pattern in grades 1 and IV education units. Many challenges are faced by PAI teachers such as changing the new learning paradigm, preparing relevant learning tools. The level of teacher satisfaction is somewhat satisfied with the positive impact on the learning process with the principle of independent learning. In conclusion, the implementation of the independent curriculum is a challenging new thing for PAI teachers. But the benefit of implementing an independent curriculum is to provide a new atmosphere and provide satisfaction in learning.